Análise em larga escala da expressão diferencial de Corynebacterium pseudotuberculosis em resposta a estresses abióticos - Anne Cybelle Pinto (2011)
A new cDNA sequencing technology has allowed deep analysis of prokaryotic transcripts. Corynebacterium pseudotuberculosis, our study target, is a bacterium responsible for several diseases, such as caseous lymphadenitis that causes important economic losses in global agrobusinesses. In this context, we characterized its differential transcriptional profile in some conditions that mimic the environment found during an infectious process, namely osmotic (2M), termic (50°C) and acid (pH=5) stresses. For this work, SOLiDTM platform was chosen to try to understand the development of the disease and modulation of the response from the genes involved in the infectious process. All transcriptionally active regions that were predicted in the genome (2057 genes) were detected, observing 97,58% of transcript genes under the control condition, and 2,42% of non-transcribed regions with a RPKM value (Reads Per Kilobase of coding sequence per Million mapped) equal to zero. During conditions of osmotic, termic and acid stresses, 98,05%, 97,34% and 97,81% of genes, respectively, were found to be transcribed. During osmotic stress, 48,01% of the transcripts were considered differentially expressed with relation to the control, whereas during termic and acid stress, 45,68% and 48,08% respectively were found. It was observed that most genes for all stresses were formed by proteins of unknown function (hypothetical), highlighting the need for more information about this microorganism. Our analysis revealed a strong relationship between acid stress response and gene expression of genes previously associated to virulence. The process of transcription regulation and cell adhesion are among the main results of Blast2GO. During osmotic stress, repair process and transmembrane transport, as well as adhesion process, were highlighted. During heat shock, fewer differentially expressed genes were part of the analysis and oxidoreduction processes and ATP catabolic process were among the main energy generators for cell survival in the hostile environment. Within the core estimulon (genes shared between the stresses), virulence genes stood out, demonstrating that already at the beginning of the exponential phase the bacteria regulates the transcription for a specific and adaptive response. Among the repressed genes, those involved in metabolic and biosynthesis were the most represented, demonstrating reduced growth, an important strategy for adjusting cell physiology to a new condition. The present study allowed the creation of a gene catalog that can be used as a resource for survival in adverse environments and escape of the host immune response. These results allow us to suggest, in future studies, possible candidates for efficient vaccines regarding potential loss reduction in agribusinesses.